2016
DOI: 10.3892/etm.2016.3173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of targeted nursing applied to SLE patients

Abstract: The aim of the present study was to evaluate the efficacy of targeted nursing for patients with systemic lupus erythematosus (SLE). A total of 114 patients clinically diagnosed with stable SLE were prospectively selected. The patients were randomly divided into the regular special nursing group, comprising 56 patients and the targeted nursing group (i.e., taylor made according to different pathogenic conditions and treatment period), comprising 58 patients. The patients received standard medical treatment for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 13 publications
0
22
0
6
Order By: Relevance
“…Last positive RCT was performed in SLE. 13 This study showed that targeted nursing by specialised nurses including an education during the hospitalisation, a personalised treatment plan and a follow-up after the hospital was better to improve adherence than regular specific nursing. However, these positive results were in balance with three RCTs which showed negative results: two of them assessed the efficacy of repeated collective education program in RA 14 15 and the other proposed a multimedia support to educate RA patients.…”
Section: Resultsmentioning
confidence: 80%
“…Last positive RCT was performed in SLE. 13 This study showed that targeted nursing by specialised nurses including an education during the hospitalisation, a personalised treatment plan and a follow-up after the hospital was better to improve adherence than regular specific nursing. However, these positive results were in balance with three RCTs which showed negative results: two of them assessed the efficacy of repeated collective education program in RA 14 15 and the other proposed a multimedia support to educate RA patients.…”
Section: Resultsmentioning
confidence: 80%
“…5,6 Among the factors likely to improve treatment adherence, TPE has been the most extensively studied, and this approach is supported by the highest level of evidence. [7][8][9][10][11][12] Consequently, we implemented a TPE program in our department, with the aim of encouraging patients to self-manage subcutaneous biotherapies. France's national authority of health (Haute Autorité de Santé, HAS) recommended structuring TPE in four stages (educational diagnosis, educational objectives, education, and assessment) in individual consultations or group sessions.…”
Section: Introductionmentioning
confidence: 99%
“…Genellikle 15-45 yaş arası doğurganlık döneminde olan genç kadınları etkilemektedir. 1,2 Hastalık; yüzde kelebek raş, ciltte oval-kırmızı döküntülü lekeler (diskoid), ciltte güneş hassasiyeti, ağızda yaralar, ağrı, ateş, yorgunluk, kilo kaybı, artrit, plörezi, perikardit, böbrek problemleri ve nörolojik problemlerle kendini göstermektedir. Antinükleer antikorlar (ANA), anti dsDNA, anti Smith ya da antifosfolipid testleri, hemoglobin, lökosit ve trombosit sayılarında düşüklükle tanılanabilmektedir.…”
Section: Introductionunclassified
“…2 Tüm kronik hastalıklarda olduğu gibi bu bireylerde de yeterli hemşirelik bakımı, tedavinin sağlanması ve desteklenmesi, hem aile hem de hasta bireye gerekli eğitimin verilmesi, sekonder kayıpların önlenmesi, yaşam kalitelerinin artması ve dolayısıyla hastalığa uyumun sağlanmasında çok önemlidir. 1,2,4…”
Section: Introductionunclassified
See 1 more Smart Citation